Back to Basics for Economics. (Wilson Quarterly)
The article discusses the failure of economists in academia in the U.S. to predict the serious impact of the 2008-2009 U.S. financial crisis, according to the article "Economics in Crisis," by J. Bradford DeLong, published in the May 2011 issue of "The Economists' Voice" magazine. Topics include DeLong's suggestion that economic departments increase the study of cognitive bias and microstructure, and the neglect of economists to appreciate the human and historical aspects of economic activity.